White fragility: Why it's so hard for white people to talk about racism - DiAngelo, Robin J. (Beacon Press, 2018)
« In this groundbreaking and timely book, antiracist educator Robin DiAngelo deftly illuminates the phenomenon of white fragility. Referring to the defensive moves that white people make when challenged racially, white fragility is characterized by emotions such as anger, fear, and guilt, and by behaviors including argumentation and silence. These behaviors, in turn, function to reinstate white racial equilibrium and prevent any meaningful cross-racial dialogue. In this in-depth exploration, DiAngelo explores how white fragility develops, how it protects racial inequality, and what we can do to engage more constructively. »--Page 4 de la couverture.
Keywords: 2000-2009; 2000-2029; amériques; antiracisme; approches et analyses; discipline; discours dominant; fem1000; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppression; épistémologie; états-unis

La construction sociale de la pensée féministe noire - Hill Collins, Patricia (Genre, postcolonialisme et diversité de mouvements de femmes, 2018)
Keywords: 1900-1999; amériques; approches et analyses; discipline; fem1000; féminismes noirs; premier cycle; périodes historiques; ressource en ligne; régions géographiques; savoirs; sciences humaines; épistémologie; états-unis